Estimation of Acacia melanoxylon unbleached Kraft pulp brightness by NIR spectroscopy - Santos, António J. (2015)
Aim of the study: The ability of NIR spectroscopy for predicting the ISO brightness was studied on unbleached Kraft pulps of Acacia melanoxylon R. Br. Area of study: Sites covering littoral north, mid interior north and centre interior of Portugal. Materials and methods: The samples were Kraft pulped in standard identical conditions targeted to a kappa number of 15. A Near Infrared (NIR) partial least squares regression (PLSR) model was developed for the ISO brightness prediction using 75 pulp samples with a variation range of 18.9 to 47.9 %. Main results: Very good correlations between NIR spectra and ISO brightness were obtained. Ten methods were used for PLS analysis (cross validation with 48 samples), and a test set validation was made with 27 samples. The 1stDer pre-processed spectra coupling two wavenumber ranges from 9404 to 7498 cm-1 and 4605 to 4243 cm-1 allowed the best model with a root mean square error of ISO brightness prediction of 0.5 % (RMSEP), a r2 of 99.5 % with a RPD of 14.7. Research highlights: According to AACC Method 39-00, the present model is sufficiently accurate to be used for process control (RPD ≥ 8).